1986
DOI: 10.1017/s0308229600016329
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of piglet mortality with behavioural observations

Abstract: Preweaning mortality generally accounts for 10-20% of all piglets born alive. A better understanding of the reasons for this mortality should help reduce losses.Data from 493 litters born over a period of 18 months were analysed to investigate the timing, apparent cause and predisposing factors of piglet mortality.To examine in more detail the way in which deaths occur a continuous video recording was made for the first 48 h. after farrowing for 31 litters. The way in which any deaths happened and the events l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
5
7
0
2
Order By: Relevance
“…Miscellaneous disorders caused the second highest mortality and the main cause was crushing of new born by mother. Similar finding was also reported by Ramesh and Sivakumar (2007) and Edwards et al (1986). This can be explained by the fact that after farrowing in the side lie posture, the gilts stand up for a moment during the initial period and major movement of gilts occurs in pen more frequently than in crate because of availability of more space.…”
Section: Discussionsupporting
confidence: 87%
“…Miscellaneous disorders caused the second highest mortality and the main cause was crushing of new born by mother. Similar finding was also reported by Ramesh and Sivakumar (2007) and Edwards et al (1986). This can be explained by the fact that after farrowing in the side lie posture, the gilts stand up for a moment during the initial period and major movement of gilts occurs in pen more frequently than in crate because of availability of more space.…”
Section: Discussionsupporting
confidence: 87%
“…Weak and low weight piglets have much higher pre-weaning mortality than piglets of average weight (Edwards, Malkin and Spechter, 1986;Gardner, Hird and Franti, 1989), especially if they are born in large litters or in litters with great weight variation (English and Smith, 1975). Weak and low weight piglets have much higher pre-weaning mortality than piglets of average weight (Edwards, Malkin and Spechter, 1986;Gardner, Hird and Franti, 1989), especially if they are born in large litters or in litters with great weight variation (English and Smith, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…One aim of the traditional farrowing crate, which has influenced its overall design, has been to restrict the sows' movement to reduce preweaning mortality attributable to crushing. An observation by Edwards and Malkin (1986) and Marchant et al (1996) showed that posterior crushing (when the sow changes from a standing to sitting position and traps piglets under her back legs) is one of two major movements performed by the sow that kills piglets. The other occurs when sows lie from a sitting position and piglets are trapped beneath her thorax.…”
Section: Productionmentioning
confidence: 99%